2018
DOI: 10.1136/tobaccocontrol-2018-054288
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure during pregnancy: a cross-sectional analysis of data from Demographic and Health Survey from 30 low-income and middle-income countries

Abstract: We have demonstrated that SHS exposure during pregnancy is far more common than active smoking in LMICs, accounting for more stillbirths than active smoking. Protecting pregnant women from SHS exposure should be a key strategy to improve maternal and child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 26 publications
4
49
0
Order By: Relevance
“…Exposure to passive smoking in this study was similar for those who lived in district (urban) and those that lived in municipality (rural). A previous study indicated that urban households have lower exposure to passive smoking [13]. Likewise, a study on secondhand smoke exposure from 26 countries revealed that passive smoking is higher in urban areas relative to rural ones [14].…”
Section: Demographic Characteristics Of Passive Smokersmentioning
confidence: 94%
See 2 more Smart Citations
“…Exposure to passive smoking in this study was similar for those who lived in district (urban) and those that lived in municipality (rural). A previous study indicated that urban households have lower exposure to passive smoking [13]. Likewise, a study on secondhand smoke exposure from 26 countries revealed that passive smoking is higher in urban areas relative to rural ones [14].…”
Section: Demographic Characteristics Of Passive Smokersmentioning
confidence: 94%
“…Similarly, the data also revealed that Indonesian boys are more likely to be exposed to passive smoking than girls (61.7% and 51.7% respectively) [12]. That said, passive smoking is known to be a higher risk factor to stillbirths (14% in Indonesia) than active smoking behavior [13]. Hence, protecting women and girls from passive smoking is critical, especially women of childbearing age, and can be a key strategy to improve the health of women and children.…”
Section: Demographic Characteristics Of Passive Smokersmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies examining the association of education and income with SHS exposure during pregnancy are limited [4][5][6][7][8][9][10][11], while there is substantial evidence that those with lower education and/or lower income are more exposed to SHS than higher ones in the general population [1,[12][13][14][15][16]. Although education and income re ect the central dimension of social strati cation, they have different meanings in society; education is thought to capture knowledge and skills, while income measures material resources to enhance health [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although education and income re ect the central dimension of social strati cation, they have different meanings in society; education is thought to capture knowledge and skills, while income measures material resources to enhance health [17]. Existing studies among pregnant women have mainly focused on education [4,6,[8][9][10][11], and the association between income and SHS exposure have rarely been examined [5,7]. To the best of our knowledge, no studies have examined the association of education and income with SHS exposure during pregnancy in Japan.…”
Section: Introductionmentioning
confidence: 99%